Quality of life over 5 years after a breast cancer diagnosis among low‐income women: Effects of race/ethnicity and patient‐physician communication. Issue 6 (19th November 2014) - Maly, Rose C.; Liu, Yihang; Liang, Li‐Jung; Ganz, Patricia A.
<x xml:space="preserve">Abstract</x> BACKGROUND The current study was performed to identify risk factors for a lower quality of life (QOL) among low‐income women with breast cancer (BC), with an emphasis on the impact of patient‐physician communication. In addition, ethnic/racial group differences in QOL changes over time were examined. METHODS A longitudinal study was conducted among 921 low‐income women with BC. Patients were interviewed at 6 months, 18 months, 36 months, and 60 months after their diagnosis of BC. Mixed‐effect regression models were performed to investigate predictors for and time effects on QOL. The main outcomes included the Medical Outcomes Study Health Survey Short Form‐36 Mental Component Summary scale (SF‐36 MCS), Medical Outcomes Study Health Survey Short Form‐36 Physical Component Summary scale (SF‐36 PCS), and the Ladder of Life scale. Chief independent variables included physician information‐giving and patient self‐efficacy in interacting with physicians. RESULTS There were no significant changes noted over time in QOL except with regard to physical functioning, with survivors reporting a significant decrease over time (P<.0001). Mean SF‐36 MCS and SF‐36 PCS scores were lower than national general population norms at all time points. Both patient self‐efficacy in interacting with physicians and physician information‐giving were found to be positively associated with the SF‐36 MCS (P = .03 and P = .02, respectively) and Ladder of Life (P = .01 and P = .03, respectively) scales. Latinas who were less acculturated reported higher SF‐36 MCS and SF‐36 PCS scores (P<.0001 and P = .01, respectively) and better global QOL (P<.0001) than white women. CONCLUSIONS Low‐income women with BC experienced poor physical and mental health. The results of the current study suggest that QOL among low‐income women with BC would be enhanced by interventions aimed at empowering patients in communicating with physicians and increasing the amount of information provided by physicians. Cancer 2015;121:916–926. © 2014 American Cancer Society.